СОЦИАЛЬНЫЕ, КУЛЬТУРНЫЕ И ЯЗЫКОВЫЕ ОСОБЕННОСТИ МЕНТАЛЬНОГО ЛЕКСИКОНА РУССКИХ И МАКЕДОНЦЕВ (Philological Studies, 2019)
Human’s world view and its lexical expression are fixed in the mental lexicon. The analysis of the mental lexicon allows us to reveal relevant to a human social, cultural and linguistic characteristics. The subject of the study is manifestation of social, cultural and linguistic characteristics in the actual lexicons (the base of the mental lexicon) of Russians and Macedonians. The material has shown that the hierarchy of the social, cultural and linguistic characteristics depends not only on the conditions of life, but also on a speaker's native language. The language provides continuity of social traditions and cultural patterns in the society.
Keywords: cultural memory, mental lexicon, actual lexicon, lexical-semantic group, human, culture, language